Acute Intermittent Porphyria: A Rare Inborn Error of Haem Metabolism - Ferdous, Md; Syeed, Abu; Hoque, Md Gofranul (Medicine Today, 2014)
A 22 year young boy presented with recurrent abdominal pain, generalized weakness & wasting with hypertension in Medicine ward CMCH. Subsequently he was diagnosed as a case of Acute Intermittent Porphyria (AIP). Though not common, any patient with unexplained abdominal crisis specially young with any peripheral or central nervous system dysfunction should raise the clinician's suspicion of being porphyric patient as prompt management can relieve the patient from progressive neurological damage and disability. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17929 Medicine Today 2013 Vol.25(2): 93-95